Nusa Toleransi Terindah (NTT) untuk Merawat Nilai-Nilai Pendidikan Multikutural di SMA Negeri 8 Kota Kupang dalam Perspektif Kearifan Lokal - Amirulah Datuk; Syahya N. Nobisa (Ideas Publishing, 2021)
The country of Indonesia is one of the largest multicultural countries in the world, this can be seen from the socio-cultural and geographical conditions of Indonesia which are so complex, diverse and extensive. Indonesia consists of various ethnic, cultural, and religious groups. The findings show that the ethnological world of education in SMA Negeri 8 Kupang is filled with students from various religions, ethnicities and races who in class or outside the classroom can learn each other. In fact, education in SMA Negeri 8 Kupang adheres to a philosophy that the people of Kupang believe in